New insights into chitosan-Ag nanocomposites synthesis: Physicochemical aspects of formation, structure-bioactivity relationship and mechanism of antioxidant activity - Hileuskaya, Kseniya; Kraskouski, Aliaksandr; Ihnatsyeu-Kachan, Aliaksei; Saichuk, Anastasiia; Pinchuk, Sergei; Nikalaichuk, Viktoryia; Ladutska, Alena; Kulikouskaya, Viktoryia; Neves, Marcia C.; Freire, Mara G.; Kim, Sehoon (Elsevier BV, 2025)
Herein, a novel approach to the controlled formation of chitosan-Ag nanocomposites (NCs) with different structures and tunable chemical/biological properties was proposed. The chitosan-Ag NCs were obtained using hydrothermal synthesis and varying the concentrations of components. The hypothesis of chitosan-Ag NC synthesis using polysaccharide coils as a "microreactor" system was confirmed. A comparative analysis of the physicochemical characteristics of the NCs with single-core-shell and multi-core-shell structures was carried out, and the "structure-property" relationship was revealed. The obtained NCs exhibited excellent antiradical properties, comparable to the activity of phenolic acids: the IC50 values were 0.051, 0.022, and 0.019 mg/mL for CS7, CS5, and caffeic acid, respectively. A mechanism for the antiradical activity of chitosan-Ag NCs was discussed. The redox activity of the NCs was found to be 11.4 and 2.3 mg ABTS per 1 mg of Ag in CS5 and CS7, respectively. The proposed environmentally friendly one-pot, one-step synthesis of silver nanoparticles inside chitosan "microreactors" represents an innovative approach to designing hybrid materials with nanoscale control of desired structure and properties. These findings pave the way for further optimization of biopolymer-silver nanostructures for various biomedical and industrial applications, including the design of a new type of hybrid catalysts such as nanozymes.